2019
DOI: 10.1080/10942912.2019.1689998
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive components of malted millet (Pennisetum glaucum), Soy Residue “okara” and wheat flour and their antioxidant properties

Abstract: This study evaluated bioactive components and antioxidant properties of malted millet, soy residue "okara" and wheat flour. The flour extracts were screened for phenolic content, flavonoid content and total antioxidant capacity using standard methods. The antioxidant activities of the studied flours to scavenge 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical, reduce iron (111) chloride and inhibit lipid peroxidation and nitric oxide (NO) were determined spectrophotometrically and the effective concentration (IC 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 40 publications
(41 reference statements)
1
5
0
Order By: Relevance
“…Pearson's correlation coefficient between the total phenolic and flavonoid contents, and various bioactivities including antioxidant and anti-inflammatory activities and cell viability determined for WS and NS is exhibited in Figure 5. As mentioned previously, phenolic compounds and flavonoids are natural antioxidants of plant materials [21,22]. Therefore, positive correlations were found significantly between total phenolic and flavonoids contents with all antioxidant activities determined by three different assays, which are DPPH, ABTS, and reducing power assays.…”
Section: Pearson's Correlation Coefficientsupporting
confidence: 53%
See 1 more Smart Citation
“…Pearson's correlation coefficient between the total phenolic and flavonoid contents, and various bioactivities including antioxidant and anti-inflammatory activities and cell viability determined for WS and NS is exhibited in Figure 5. As mentioned previously, phenolic compounds and flavonoids are natural antioxidants of plant materials [21,22]. Therefore, positive correlations were found significantly between total phenolic and flavonoids contents with all antioxidant activities determined by three different assays, which are DPPH, ABTS, and reducing power assays.…”
Section: Pearson's Correlation Coefficientsupporting
confidence: 53%
“…Phenolic compounds and flavonoids are natural antioxidants that are known to be responsible for the antioxidant activity of plant materials [21,22]. The major phenolic compounds of wheat grain are ferulic acid, catechin, epigallocatechin gallate and luteolin [23].…”
Section: Total Phenolic and Flavonoid Contentsmentioning
confidence: 99%
“…BSs are known for having anthocyanins a compound that is responsible for the phenolic content of the grain. Anthocyanin is a heat‐sensitive compound, and this might be the reason that after boiling phenolic and flavonoid contents showed a distinct decrease, however phenolic and flavonoid content of the BS‐based okara was still found to be higher than the value previously reported in okara by Ibidapo et al 45 …”
Section: Resultsmentioning
confidence: 62%
“…14,44 BSs are known for having anthocyanins a compound that is responsible for the phenolic content of the grain. Anthocyanin is a heat-sensitive compound, and this might be the reason that after boiling phenolic and flavonoid contents showed a distinct decrease, however phenolic and flavonoid content of the BS-based okara was still found to be higher than the value previously reported in okara by Ibidapo et al 45 Antioxidants are substances that combat free radicals by interfering at any one of the three key steps of the free radical mediated oxidative process, namely initiation, propagation, and termination. 46 These antioxidants are also produced by biological systems and are found in many foods naturally, and the balance between oxidants and antioxidants determines health and vitality.…”
Section: Minerals Antinutritional and Element Analysismentioning
confidence: 81%
“…15 Studies have shown that reactive oxygen species reacted with free radicals generated during cellular metabolism could play a significant role in chronic disease pathogenesis, including cancer and coronary heart disease. 16 Hence, dietary antioxidants can act as an inhibitor in combating the free radicals and reactive oxygen species, thereby reducing the risk of chronic diseases. Therefore, in this study, we are interested in evaluating the effectiveness of fermentation using various food-grade microorganisms in increasing TPC and TFC.…”
Section: Introductionmentioning
confidence: 99%